Process Evaluation of a Residential Substance Abuse Treatment (RSAT) Program in Dallas County, Texas, 1998-1999 - Hiller, Matthew L. ([Verlag nicht ermittelbar], 2003)
This study assessed the Dallas County Judicial Treatment Center (DCJTC) in Texas. The DCJTC is a residential substance abuse treatment center for drug-involved felony offenders. It provides a treatment program of approximately six months in three major phases: orientation, main treatment, and re-entry. Data were collected from 429 offenders admitted to the DCJTC between January and December 1998. During their first week of treatment, residents completed a comprehensive intake battery that included (1) the Texas Christian University (TCU) initial assessment, (2) the TCU self-rating form (SRF), and (3) the TCU intake interview. The initial assessment gauged mental status, background and psychosocial functioning, alcohol and other drug use, and psychological status. The SRF assessed psychological functioning, social functioning, and motivation for treatment. The intake interview included detailed questions on the resident's social background, family and peer relations, health and psychological status, criminal history, drug use problems, and behavioral risks for HIV/AIDS. Progress made during treatment was measured by the TCU Resident Evaluation of Self and Treatment (REST) and the TCU Counselor Rating of Client (CRC) forms. The REST included all questions on the SRF, plus questions on offenders' perceptions of the structure of the program and their experiences while in treatment, an evaluation of the counselor, an evaluation of their own personality, and ratings of group and individual treatment sessions. The CRC forms rated residents on a set of attributes related to residents' ability to benefit from treatment and indicated the extent to which counseling activities with each client had focused on certain activities.